The Effect of Malt Extract on The Lactic Acid Bacteria (LAB) Population And the Lactobacillus Numbers In The Intestine and Crop of Broiler Chickens - Talazadeh , Forough; Houshmandi, Kiavash (Journal of Poultry Sciences and Avian Diseases, 2025)
In order to study the effect of malt extract on lactic acid bacteria (LAB) population and the Lactobacillus numbers in intestine and crop of broiler chickens, a total of 120 day-old broiler chicks, Ross strain, were purchased and divided into 4 equal groups. Each group divided into 3 subgroup of 10 chicks. Group A , B and C chickens received 0.2% , 0.3% and 0.5% of malt extract respectively in drinking water. Group D chickens did not get malt extract. For determination of Lactobacillus and lactic acid bacteria counts, at the end of the period, three chicks of each subgroup (9 chicks of each treatment) were chosen randomly. One gram of the crop and ileo-cecum content were taken and cultured on MRS for determination of lactic acid bacteria counts and Lactobacillus distinction respectively. The results of this study showed that receiving of malt extract could increase lactobacillus counts of intestine compared to control group. Also receiving of 0.3% of malt extract could increase lactobacil counts of crop compared to all groups. So it concluded that malt extract influences beneficial microflora of intestine and crop.